2012
DOI: 10.4103/2277-9531.100160
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between health literacy, health status, and healthy behaviors among older adults in Isfahan, Iran

Abstract: Background:Health literacy is a measure of an individual's ability to read, comprehend, and act on medical instructions. Limited health literacy can reduce the adults’ ability to comprehend and use basic health-related materials, such as prescription, food labels, health education pamphlets, articles, appointment slips, and health insurance plans, which can affect their ability to take appropriate and timely health care action. Nowadays, low health literacy is considered a worldwide health threat. So, the purp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
69
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(89 citation statements)
references
References 24 publications
(39 reference statements)
7
69
3
Order By: Relevance
“…In the present study, the age of the subjects did not correlate statistically with the educational level of individuals, which is consistent with the previously described [24]. Some authors have shown that older people had a lower level of literacy [40,49] and, consequently, had worse oral health that was inconsistent with the current study. The reason for this difference can be attributed to the type of study so that the present study was conducted only on pregnant women and the age range was not high.…”
Section: Discussionsupporting
confidence: 85%
“…In the present study, the age of the subjects did not correlate statistically with the educational level of individuals, which is consistent with the previously described [24]. Some authors have shown that older people had a lower level of literacy [40,49] and, consequently, had worse oral health that was inconsistent with the current study. The reason for this difference can be attributed to the type of study so that the present study was conducted only on pregnant women and the age range was not high.…”
Section: Discussionsupporting
confidence: 85%
“…Research article Our findings were consistent with an existing body of international and national evidence. The findings of several national studies suggest a relatively low level of health literacy in the Islamic Republic of Iran (14,15,(20)(21)(22)(23). For instance, in a study among the literate urban population > 44% of participants had inadequate and only 16% had adequate health literacy levels (16).…”
Section: Discussionmentioning
confidence: 99%
“…In the Islamic Republic of Iran, one of the most populated countries in the Middle East, several studies have tried to measure health literacy and reported overall insufficient health literacy levels, ranging from 41% in adults in the central province of Yazd to 68% in the southeastern province of Baluchistan (13). Previous studies have also indicated varying levels of health literacy among different subpopulations of patients, e.g., 70% insufficient health literacy in patients with diabetes (14); and age groups, e.g., 79.6% insufficient health literacy among older adults (15). However, the existing body of evidence often suffers from sampling bias (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…A systematic review study by Berkman et al examined the relationship between health literacy and health outcomes (59). Considering the importance of the relationship between HL and use of health outcomes, health care services and costs, it is crucial to consider population 6 Health Scope. 2018; 7(3):e62212.…”
Section: Discussionmentioning
confidence: 99%
“…Health Literacy has been introduced by the World Health Organization (WHO), as a key determiner of healthcare. It has been recommended globally to create an association to constantly monitor and coordinate strategic activities, especially with the aim of promoting healthcare (6).…”
Section: Contextmentioning
confidence: 99%